TINGKAT KERUSAKAN DAN PADAT POPULASI HAMA Sexava coriacea L. PADA TANAMAN KELAPA DI DESA TONGUTESUNGI KECAMATAN IBU KABUPATEN HALMAHERA BARAT - Avendi Rangkaya; Maxi Lengkong; Caroulus S. Rante; James B. Kaligis (COCOS, 2021)
ABSTRACTSexava coriacea L. is a major endemic pest that attacks the leaves of coconut trees in WestHalmahera district and can cause damage so that plants cannot produce fruit and can cause plantdeath if severe attacks. This study aims to determine the level of damage and population density ofS. coriacea pests in coconut plantations in Tongutesungi Village, Ibu District, West HalmaheraRegency. The research was carried out in the coconut plantation area of Tongutesungi Village, IbuDistrict, West Halmahera Regency. Observation of the level of damage to S. coriacea was obtainedby taking five affected leaf sheaths by cutting them to drop them on the ground, then observing thedamage to coconut leaves. The number of fronds observed was 5 times 20 sample plants per 100fronds, so that the total observed fronds were 100 times 5 observation points, namely 500 fronds.Observation of population density of S. coriacea per sample tree was determined by directlycounting the number of insects both nymphs and imago found in coconut leaf midribs. Observationof population density was 4 fronds x 20 sample trees multiplied by 5 points. The observation areawas 400 fronds. The population density of S. coriacea was determined by obtaining the averagevalue of all observational data. The results of the study on the level of damage to the samplingleaves of coconut trees attacked by S. coriacea were 65.07% - 67.32% (> 50-75%) and very heavy79.19% - 81.21% (> 75-100) the average level of damage reached 65.07% - 81.21% or the averagelevel of damage from all observation locations was 74.71%. The population density of S. coriaceamidrib at all observation locations ranged from 1.87- 3.01 individuls/midrib with an averagepopulation density of 2.45 individuals/midrib.Keywords : Sexava coriacea L., Cococ nucifera L., degree of damage, population density